Konsep Upah Pekerja Nelayan di Kabupaten Asahan, Batu Bara, dan Tanjung Balai - Manurung, Mangaraja; Rambe, M. Irfan Islami; Saragih, Agrifa Leonardo; Siregar, Pangulu (Jurnal Hukum IUS QUIA IUSTUM, 2025)
The issues surrounding the uncertainty of wage for fishermen present a number of challenges that need to be overcome, including work agreements, wage provision, and social protection. The formulation of the problems in this study are: 1) factors that hinder the implementation of industrial agreements and fair wage systems on the coasts of Asahan Regency, Tanjung Balai City, and Batu Bara Regency; and 2) the concept of rights protection and a fair wage system to improve the welfare of fishermen in the said areas. Based on the mandate of Law No. 7 of 2016 on the Protection and Empowerment of Fishermen, Fish Farmers, and Salt Farmers ('UU PPNPP'), the local government is obliged to provide assistance and protection for fishermen, which to this date has not received sufficient attention. This study aims to analyse the obstacles in the implementation of fair wages through local government policies and to propose a fair wage concept to improve the welfare of fishermen in the said coastal areas. The method applied is empirical legal research, which involves collecting primary and secondary data through observation, surveys, and interviews. The research findings indicate that the UU PPNPP has regulated the protection and empowerment of fishermen in Indonesia through planning, implementation of protection, and economic empowerment. However, its implementation remains ineffective in all three research locations. The hindrances identified include income instability, limited access to facilities, and lack of adequate legal protection. Despite efforts to provide training and market access, fishery workers still face major challenges, including dependence on middlemen and limited access to modern technology. Therefore, the welfare of fishery workers requires more attention so that the mandate of the law can be implemented optimally.Keywords: Labour Welfare, Fishery Workers, Wages, Economic Protection AbstrakMasalah kepastian pengupahan bagi pekerja nelayan masih menyisakan sejumlah tantangan yang perlu diatasi, termasuk perjanjian kerja, pemberian upah, dan perlindungan sosial. Rumusan masalah dalam penelitian ini meliputi: 1) faktor yang menghambat penerapan perjanjian kerja dan sistem pengupahan yang adil di pesisir Kabupaten Asahan, Kota Tanjung Balai, dan Kabupaten Batu Bara; serta 2) konsep perlindungan hak dan sistem pengupahan yang layak untuk meningkatkan kesejahteraan buruh nelayan di daerah tersebut. Berdasarkan amanat Undang-Undang No. 7 Tahun 2016 tentang Perlindungan dan Pemberdayaan Nelayan, Pembudi Daya Ikan, dan Petambak Garam (UU PPNPP), pemerintah daerah berkewajiban memberikan pendampingan dan perlindungan bagi pekerja nelayan, yang hingga kini belum memperoleh perhatian yang cukup. Penelitian ini bertujuan untuk menganalisis hambatan dalam penerapan upah layak oleh kebijakan pemerintah daerah serta mengusulkan konsep pengupahan yang sesuai untuk meningkatkan kesejahteraan buruh nelayan di wilayah pesisir. Metode yang diterapkan adalah penelitian hukum empiris, yang melibatkan pengumpulan data primer dan sekunder melalui observasi, survei, dan wawancara. Temuan penelitian menunjukkan bahwa UU PPNPP telah mengatur perlindungan dan pemberdayaan nelayan buruh di Indonesia melalui perencanaan, pelaksanaan perlindungan, dan pemberdayaan ekonomi. Namun, implementasinya masih kurang efektif di ketiga lokasi penelitian. Permasalahan yang ditemukan meliputi ketidakstabilan pendapatan, keterbatasan akses terhadap sarana, dan kurangnya pelaksanaan perlindungan hukum yang memadai. Meski terdapat upaya untuk memberikan pelatihan dan akses pasar, buruh nelayan masih menghadapi tantangan besar, termasuk ketergantungan pada tengkulak dan akses terbatas terhadap teknologi modern. Oleh karena itu, kesejahteraan buruh nelayan memerlukan perhatian lebih agar amanat undang-undang dapat terlaksana dengan optimal.Kata Kunci: Kesejahteraan Buruh, Pekerja Nelayan, Pengupahan, Perlindungan Ekonomi